2018
DOI: 10.1142/s021797921850354x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the public transit accessibility in Changsha City, China, after the introduction of a subway network

Abstract: Using geographic information systems (GIS) network analysis technology, this paper studied the impact of new subway projects on the accessibility of an urban transit network. First, the status quo of public transit accessibility in Changsha City was estimated using two improved accessibility models: the cumulative opportunity measurement model and the gravity measurement model. Second, the topological structural information of the public transit network and basic public transit data were collected from mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Sarah et al [ 43 ], through a comparative analysis of accessibility for various modes of travel, found that the gravity model is significantly applicable to situations with different path efficiencies. Zhai et al [ 44 ], based on gravity models and opportunity models, conducted a comparative analysis of accessibility before and after the construction of urban subways, where traffic speed and transportation efficiency were identified as important influencing factors. This study focuses on the impact of water bodies on the evolution of urban road network structure and the inherent relationship between the corresponding road network structure and the overall accessibility of urban roads.…”
Section: Objects and Methodsmentioning
confidence: 99%
“…Sarah et al [ 43 ], through a comparative analysis of accessibility for various modes of travel, found that the gravity model is significantly applicable to situations with different path efficiencies. Zhai et al [ 44 ], based on gravity models and opportunity models, conducted a comparative analysis of accessibility before and after the construction of urban subways, where traffic speed and transportation efficiency were identified as important influencing factors. This study focuses on the impact of water bodies on the evolution of urban road network structure and the inherent relationship between the corresponding road network structure and the overall accessibility of urban roads.…”
Section: Objects and Methodsmentioning
confidence: 99%